A legislação brasileira na eficácia da salvaguarda das pessoas com transtorno do espectro autista: a garantia do direito fundamental à saúde - RIBEIRO, Alyssa de Sousa (2024)
This writing aims to elucidate the rule in the legal system regarding rights and guarantees as a prerogative for people diagnosed with ASD in Brazil. In this thesis, initially, the general characteristics will be addressed from a pathological aspect, corroborating concepts and their classifications, as well as diagnoses, treatment methods and development. Afterwards, the legal and constitutional scope will be explained, a legislative provision set out in the Brazilian legal system, such as Law No. 12,764/2012 and Law No. 13,146/2015, presenting their applicability with a focus on fundamental rights and principles of dignity of the human person. And finally, the dictates that involve effectiveness, bringing the reserve of what is possible to guarantee the implementation of public policies and the existential minimum as a guiding element of health policies as a safeguard for the protection of fundamental rights and health and the promotion of democracy for this group minority.